2017
DOI: 10.1152/japplphysiol.00934.2016
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of tongue mechanical properties using different contraction tasks

Abstract: Inadequate upper airway (UA) dilator muscle function may play an important role in the pathophysiology of obstructive sleep apnea (OSA). To date, tongue mechanical properties have been assessed mainly using protrusion protocol with conflicting results. Performance during elevation tasks among patients with OSA remains unknown. This study aimed at assessing tongue muscle strength, strength stability, endurance time, fatigue indices, and total muscle work, using elevation and protrusion tasks with repetitive iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
1
9
1
1
Order By: Relevance
“…In another study, lower tongue total muscle work was detected in nonobese compared to untreated obese patients with moderate to severe OSA. 49 In this study patients with OSA were also not treated, which could explain the differing results compared to our cohort. In summary, BMI seems to affect tongue fatigue in untreated nonobese patients with OSA but not in treated nonobese patients with OSA.…”
Section: Discussionmentioning
confidence: 71%
“…In another study, lower tongue total muscle work was detected in nonobese compared to untreated obese patients with moderate to severe OSA. 49 In this study patients with OSA were also not treated, which could explain the differing results compared to our cohort. In summary, BMI seems to affect tongue fatigue in untreated nonobese patients with OSA but not in treated nonobese patients with OSA.…”
Section: Discussionmentioning
confidence: 71%
“…The comparability to our study is limited since fatigue was tested in vitro after a genioglossus biopsy. In another study, lower tongue total muscle work was detected in non-obese compared to untreated obese patients with moderate to severe OSA [25]. Summarizing the studies BMI seems not to be influencing tongue fatigue in treated non-obese OSA patients but in untreated non-obese OSA patients.…”
Section: Gender Bmi and Agementioning
confidence: 87%
“…Overall results of this study showed that increased total body fat % and visceral fat % resulted in increased tongue strength during speech and swallowing tasks, respectively. While limited, other studies have shown similar results Li 13 and Ulrich Sommer. 18 Additionally, other research comparing the tongue strength of active and non-active adults shows that active adults have significantly stronger anterior and posterior maximal values.…”
Section: Tongue Strength and Obesitymentioning
confidence: 59%
“…11 Additionally, persons with moderate OSA have been shown to be more susceptible to tongue muscle fatigue. 12,13 Moreover, tongue strengthening (i.e., oropharyngeal) exercises and hypoglossal nerve stimulation have been shown to reduce the severity and symptoms for persons with moderate OSA. 14,15 Conversely, there is evidence suggesting that tongue strength may not play a role with OSA.…”
Section: Tongue Strength and Osamentioning
confidence: 99%
See 1 more Smart Citation